Individual Difference Factors in the Learning and Transfer of Patterning Discriminations - Maes, Elisa; Vanderoost, Elias; D'Hooge, Rudi; De Houwer, Jan; Beckers, Tom (Frontiers in Psychology, 2017)
In an associative patterning task, some people seem to focus more on learning an overarching rule, whereas others seem to focus on acquiring specific relations between the stimuli and outcomes involved. Building on earlier work, we further investigated which cognitive factors are involved in feature- versus rule-based learning and generalization. To this end, we measured participants’ tendency to generalize according to the rule of opposites after training on negative and positive patterning problems (i.e., A+/B+/AB- and C-/D-/CD+), their tendency to attend to global aspects or local details of stimuli, their systemizing disposition and their score on the Raven intelligence test. Our results suggest that while intelligence might have some influence on patterning learning and generalization, visual processing style and systemizing disposition do not. We discuss our findings in the light of previous observations on patterning.